PROSPECTS FOR THE DEVELOPMENT OF THE DIGITAL ECONOMY IN KAZAKHSTAN - Georgieva, E. A; Тovma N. А.; Nurmagambetova А. Z.; Akimbaeva К. Т.; Doszhan, R D; Nurkasheva Н. С. (Farabi Journal of Social Sciences, 2020)
In modern Kazakhstan, the role of advanced technologies and innovations in economic development is growing. The latest technologies allow increasing the efficiency of production and business processes. Traditional approaches and methods of work are changing as the latest technologies penetrate into new industries and spheres of human activity. In this regard, the purpose of this article is to consider the impact of digitalization on the development of the economy and determine the main directions of development of the digital economy. At the same time, modern methods of scientific knowledge, such as analysis and synthesis, are used; induction, abstraction. The article considers the growth of GDP in the conditions of digitalization, the volume of venture financing of digital projects in Kazakhstan in comparison with other countries, the economic and social advantages of digitalization of the economy, including the impact of the digital economy on the labor market. Assistance in attracting direct private investment through crowdfunding platforms is proposed as a tool for developing the digital economy. Positive effects of the digital economy are revealed. The main directions of development of the digital economy are outlined: competent it regulation, developed infrastructure, national centers of competence and digital platforms. Segments of the digital economy are highlighted: the first is software products where added value is created. The second is the level of competence where research and development takes place. This is where platforms are created that are used to create products. And the third segment includes infrastructure, qualified personnel, and the regulatory environment, which is devoted to the question of how to describe new entities that are emerging in this economy, and how to configure relationships between participants.